Experimental study of mechanical properties and residual stresses of expandable tubulars with a thread joint. (June 2017) - Xu, Shugen; Wang, Chong; Wang, Shengkun; Zhang, Lan; Li, Xinchun; Zhang, Honghai
Abstract: As the core of drilling technology in the 21st century, expandable tubular technology could solve practical engineering problems including inadequate casing displacement and high-pressure formations in drilling, and it could be applied in many fields such as well workover, cementation, and well completion. However, the difficulties of breakage and leakage at the thread joint in the expansion process limited the development of this technology. This study investigated the effect of the expansion process on various aspects of the J55 steel expandable tube involved in deformation, residual stress, mechanical properties, and microstructure variation by experimentation. The results showed that in the top and root of the box thread zone the residual stresses were relatively high. That is because much wall thickness was lost due to thread cutting in the top zone and the bending moment was generated from the cone mandrel pressing outwards in the root zone of box thread. It was noticeable that the yield and ultimate strength of the expanded tube were increased after the expansion process, which is work hardening. Furthermore, the microstructure of the unexpanded and expanded tubes was similar, and consisted of pearlite surrounded by ferrite. But in the expanded tube, the pearlite and ferrite were more uniformly and compactly distributed. Highlights: The J55 steel tubular with thread joint was expanded by cone mandrel radially. The microstructure of expanded tubular is not changed but is strength hardened. The expanded thread joint still have sealabilty with the changed geometry. The high residual stress in thread joint was generated due to irregular shape.